Legal Aspects of Corporate Responsibility for Road Damage Caused by Overdimensioned and Overloaded Transport Vehicles - Wardana Kusuma, Wisnu; Dede Amirudin; M. Popik Montanasyah; Sri Sarjana; Febrianto Fatah Yogatama (Universitas Medan Area, 2025)
This article aims to analyze the ideal construction of criminal liability for corporations responsible for violations of goods transportation with over-dimensional and overloading (ODOL) specifications. The problem is focused on the lack of effective legal framework and enforcement mechanisms to address corporate responsibility in ODOL vehicle violations that contribute to traffic accidents, road damage, and safety hazards. In order to approach this problem, a theoretical reference of corporate criminal liability and transportation law enforcement is used. The data is collected through legal research methodology including statute analysis, case studies, and regulatory examination, and analyzed qualitatively through normative legal analysis. This study concludes that an ideal construction of corporate criminal liability requires comprehensive regulations with firm government commitment, active participation from vehicle-owning companies, and strict sanctions targeting not only drivers but also their superiors and companies that order ODOL transportation, as well as vehicle owners, to create effective deterrent effects and maximize law enforcement in controlling over-dimensional and overloaded vehicles while addressing resulting problems such as traffic congestion, road infrastructure damage, and traffic accidents that may cause injuries or fatalities.